Virological Monitoring of Wastewater as an Element of Surveillance for Emergent and Re-Emergent Infections - Zadorozhna, V.I.; Liulchuk, M.G.; Podavalenko, A.P.; Malysh, N.G.; Surmasheva, O.V.; Raksha-Sliusareva, O.A.; Murashko, O.V.; Задорожна, В.І.; Люльчук, М.Г.; Подаваленко, А.П.; Малиш, Н.Г.; Сурмашева, О.В.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
The risk of biological threats has been constantly increasing in recent years. This is due both to the adaptation of avian and animal pathogens to the human organism as a result of the expansion of the area of human activity and to the development of biotechnologies. Viruses predominate among these pathogens. Examples in recent years are the COVID-19 pandemic and the continued spread of monkeypox (MPX). The situation requires the search for objects for research that would have a high informative value and could help in assessing and predicting the spread of  infections. The article analyzed and assessed the potential and importance of virological monitoring of wastewater as an element of surveillance for emergent and re-emergent infections, using the example of some of them (enterovirus infections – poliomyelitis and infection caused by enterovirus D68, COVID-19, and MPX). Monitoring of enteroviruses in wastewater is a routine practice in many countries. Poliomyelitis is subject to eradication, and its incidence is extremely low. The study of wastewater makes it possible to indirectly detect the circulation of poliovirus among people, determine its molecular genetic characteristics (“wild”, vaccine, vaccine-derived poliovirus), the duration of circulation, and ways of spread and take appropriate measures in a timely manner. Enterovirus type D68 gained relevance as a re-emergent infection starting in 2014. Large outbreaks caused by it began to be registered in the USA, Canada, and then in the European region. Previously, the virus caused minor respiratory symptoms, but now it has become the cause of severe acute respiratory disease, particularly in children, and has also acquired neurovirulent properties. Its monitoring in wastewater allows for assessing the actual intensity of the epidemic process of this infection in certain territories and in certain countries, which cannot always be done based on clinical diagnosis without an additional etiological diagnosis. During the 3 years of the pandemic, SARS-CoV-2 has taken root in the human population, but a new parasitic system continues to develop. Wastewater monitoring makes it possible to assess the intensity of the epidemic process of COVID-19, which is supported by manifest forms of infection, asymptomatic persistence of the virus, and convalescents. It also allows for analyzing the effectiveness of quarantine and other restrictive measures, detecting genetic changes in the virus and trends in the formation of new variants of the virus. Since May 2022, MРХ has gone beyond the borders of endemic countries and began to spread rapidly, acquiring the character of a re-emergent infection. A variant of the pathogen (clade 3) began to evolve and became transmissible from person to person. The disease it causes began to radically differ from the previously known MRC due to changes in pathogenesis and epidemiological features. First of all, this concerns the pronounced anthroponotic characteristics of re-emergent MРХ in comparison with the zoonotic manifestations of the previously known endemic MРХ. The article discusses the results of studies conducted in different countries on the determination of MPX virus (MPXV) nucleic acids in wastewater samples using OPG002 gene analysis of all MPXVs (G2R_G), the West African clade (G2R_WA), and virus reference genomes of  MPXV of the outbreak in 2022 (G2R_NML). Thus, virological monitoring of wastewater can be used as an effective element of surveillance for most infectious diseases, in particular, emergent and re-emergent ones.